Mechanical Properties of Tailings Sample with Different Moisture Contents under Dry and Wet Cycles - Ling-ling Wu; Yao-hui Guo; Kai-wen Tong; Lin Hu; Qing Yu; Zhi-jun Zhang (Advances in Civil Engineering)
Due to precipitation infiltration, evaporation of water, and rising and falling of the wetting line, the tailings are in a cyclical moisture absorption-dehumidification state for a long time. The mechanism of change of physical and mechanical properties of tailings during the dry and wet cycle is related to the safe operation of the entire tailings dam. In order to explore the variation of the mechanical behavior of tailings in a tailings pond in Hunan Province with the number of dry and wet cycles under different initial water content conditions, the tailings sand samples with moisture content of 6.10%, 10.40%, 14.00%, 18.20%, and 21.00% were subjected to 0 to 6 times of moisture absorption and desorption cycles at natural dry density, and then, the stress-strain relationship curves, pore water pressure, failure mode, and shear dilatancy of these samples were tested by triaxial consolidation undrained shear test. The test results showed that when the number of moisture absorption and desorption cycles increases, the strength of the tailings sand sample was weakened, and the strength tended to be stable after 3∼5 cycles. In addition, the stress-strain curve of the sample with lower water content dropped sharply. However, the pore pressure of tailings sand samples with different water contents under different wet and dry cycles all showed a phenomenon of increasing first and then decreasing in general.